2011
DOI: 10.1093/cid/ciq107
|View full text |Cite
|
Sign up to set email alerts
|

A Dog-Associated Primary Pneumonic Plague in Qinghai Province, China

Abstract: Dogs are believed to be an indicator animal for plague surveillance, but their association with PPP is rare. Our results provide evidence for this possibility, which suggests the public health significance of dogs as a source of plague.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 25 publications
2
82
0
3
Order By: Relevance
“…Pneumonic plague can then be spread from person to person via respiratory droplets generated from the sneezing and coughing of patients. 4 Without timely and proper treatment, mortality is very high for plague. 1 Currently, there is not an ideal plague vaccine for human use.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonic plague can then be spread from person to person via respiratory droplets generated from the sneezing and coughing of patients. 4 Without timely and proper treatment, mortality is very high for plague. 1 Currently, there is not an ideal plague vaccine for human use.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that antibodypositivity prevalence among dogs and cats from the Ceará plague foci, and from Chapada da Borborema (PB), were similar 13,22 . During a plague outbreak in a village in Yunnan Province, China serum-positivity rates in domestic cats and dogs were 23.5% and 26.5%, respectively 23 . This could be because many diseased cats do not survive the infection, while dogs are more resistant and more likely to recover 10 .…”
Section: Yearmentioning
confidence: 99%
“…In coyotes from urban areas in California, titers ranged from 1/16 to 1/1,024 26 . In plague areas of China, titers varying from 1/40 to 1/1,280 were found in 49 domestic dogs 23 .…”
mentioning
confidence: 99%
“…27 Another outbreak of pneumonic plague occurred in Qinghai Province of China (north of Tibet) in 2009 affecting 12 persons, of whom three died. 5 The index case was a herdsman exposed to a sick 6 At a different rural focus in Algeria in 2008, four nomads acquired plague, resulting in one death from pneumonia. 7 The disease re-emerged also in Libya in 2009, affecting five persons with one fatality, after an absence of reported cases for 25 years.…”
Section: Reported Occurrence Worldwidementioning
confidence: 99%
“…The purpose of this review is to examine the importance of plague during the first decade of this century with an emphasis on novel events and progress of clinical knowledge (Table 1). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Relevant literature was obtained by searching Pubmed for papers covering the years 2000-2009.…”
Section: Introductionmentioning
confidence: 99%